Analysis of guidelines for the developing the NFT digital art industry in Zhejiang Province, the people's Republic of China - Vanitwatthananuwat, Chaiyot; Xinlong, Tang (Journal of Rattana Bundit University, 2024)
The NFT digital art industry in Zhejiang Province, People's Republic of China, is currently navigating challenges related to technology implementation, regulation, intellectual property rights, platform model management, and the development of the digital asset industry. These factors are critical mechanisms for the advancement of the NFT digital art sector. The objectives of this research were to: (1) study and analyze the patterns of digital art platforms, and (2) examine the developmental direction of the digital asset industry within the digital art market in Zhejiang Province. This study employed a qualitative research design, using in-depth interviews as the primary method. Six experts participated in the study, including two from the digital art industry, two from the digital art business, one specializing in digital platforms, and one scholar in cultural innovation. The interview data were analyzed using content analysis. The findings revealed that the digital art platform landscape in Zhejiang Province is in its early stages, yet it holds significant potential for developing NFT digital platforms. Over 700 related platforms have been established by various companies, with a strong focus on compliance with regulations and legal measures. Efforts are also being made to promote the construction of a robust digital art ecosystem, enhance the safety and stability of digital assets, and strengthen platform management. Furthermore, the study identified several development guidelines for the digital art industry in Zhejiang Province. These include fostering market development and collaboration, enhancing creation and production processes, advancing technology and platform construction, and implementing effective risk regulation and control measures. Management strategies were also highlighted, emphasizing the importance of developing copyright certification and infringement prevention mechanisms, building a transparent and efficient digital art marketplace, and ensuring the security of digital assets.